2004
DOI: 10.1074/jbc.m404679200
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Dependence of the Ca2+-selective TRPV6 Channel

Abstract: ⌬695-725 , which lacks the C-terminal domain required for Ca 2؉ -calmodulin binding, does not form constitutive active channels, whereas the human TRPV6 D542A , carrying a point mutation in the presumed pore region, does not function as a channel. In summary, no constitutive open TRPV6 channels were detected in patch-clamp experiments from transfected HEK cells. However, channel activity is highly regulated by intracellular and extracellular divalent cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 20 publications
6
46
0
Order By: Relevance
“…The inactivation of TRPV6 is characterized by a slow decline after an initial fast inactivation phase, whereas TRPV5 only shows the slow inactivation phase (Nilius et al 2001a. In line with a Ca 2+ -dependent regulation is the observation that chelation of intracellular Ca 2+ with ethylene glycol-bis(b-aminoethyl ether)-N,N,N′,N′-tetra acetic acid (EGTA) or 1,2-bis(2-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid acethoxymethylester (BAPTA) resulted in increased channel activity (Bodding and Flockerzi 2004;Hoenderop et al 2001b;Peng et al 1999). Together, these data indicate that intracellular Ca 2+ exerts a negative feedback mechanism on TRPV5 and TRPV6 activity.…”
Section: Ca 2+ -Dependent Inactivationmentioning
confidence: 88%
“…The inactivation of TRPV6 is characterized by a slow decline after an initial fast inactivation phase, whereas TRPV5 only shows the slow inactivation phase (Nilius et al 2001a. In line with a Ca 2+ -dependent regulation is the observation that chelation of intracellular Ca 2+ with ethylene glycol-bis(b-aminoethyl ether)-N,N,N′,N′-tetra acetic acid (EGTA) or 1,2-bis(2-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid acethoxymethylester (BAPTA) resulted in increased channel activity (Bodding and Flockerzi 2004;Hoenderop et al 2001b;Peng et al 1999). Together, these data indicate that intracellular Ca 2+ exerts a negative feedback mechanism on TRPV5 and TRPV6 activity.…”
Section: Ca 2+ -Dependent Inactivationmentioning
confidence: 88%
“…A recent study reported that IGF-1 is secreted by Ca 2 þ -triggered exocytosis 24 it was later shown that this is likely due to an effect of fura-2 in buffering intracelluar [Ca 2 þ ], because patch-clamp recording indicated no spontaneous channel activity. 41 It is now understood that TRPV5/6 channels are negatively regulated by extracellular [Ca 2 þ ], and that lowering extracellular [Ca 2 þ ] can increase the channel conductance to monovalent cations such as Na þ . 24,40,42 Membrane depolarization has been shown to activate the PI3K-Akt signaling in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitation was performed using the 4G10 or anti-p85 antibodies following previously published protocol. 41 The immunoprecipitated complex was analyzed by western blot using anti-p85, anti-PDK1, and 4G10 antibodies as described above. The ratios of phosphorylated to total protein were calculated after the images had been analyzed by densitometry using a Fluor-S Imager (Bio-Rad) and ImageJ software.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even high concentrations of fast exogenous Ca 2ϩ chelators are unable to control the microdomain in the close proximity of the channel (9). Thus, the physiological activation mechanism of TRPV6 is not clear because no current was detected under in vivo Ca 2ϩ buffering conditions (10).…”
Section: The Transient Receptor Potential (Trp)mentioning
confidence: 99%